10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Background Hip arthroscopy effectively treats femoroacetabular impingement syndrome (FAIS), but persistent pain may be related to concomitant extra-articular pathology such as subspine impingement syndrome (SSI). Standard diagnosis of SSI often relies on 3-dimensional computed tomography (3D-CT) morphology (Hetsroni type II/III), although this morphology is common in individuals who are asymptomatic and correlates poorly with symptoms. Purpose To compare minimum 2-year clinical outcomes after arthroscopic subspine decompression in patients with concurrent FAIS and type II/III anterior inferior iliac spine (AIIS) morphology, stratified by diagnostic method: 3D-CT morphology alone versus 3D-CT morphology plus a positive ultrasound-guided diagnostic injection. Study design Cohort study; Level of evidence, 3. Methods This study included patients aged 18 to 55 years with type II/III AIIS morphology who underwent primary hip arthroscopy for FAIS and SSI between January 2021 and November 2023 and had minimum 2-year follow-up. Patients diagnosed by CT morphology alone (CT classification group) were propensity score matched 1:1 to patients with a positive ultrasound-guided AIIS injection (injection group), with 57 patients per group. Matching variables were age, sex, body mass index, lateral center-edge angle, alpha angle, Tönnis grade, and Beighton score. All patients underwent arthroscopic subspine decompression. Patient-reported outcomes and rates of achieving the minimal clinically important difference, Patient Acceptable Symptom State (PASS), and substantial clinical benefit (SCB) were compared. Results Preoperative patient-reported outcome scores were similar between groups (all P > .05). At minimum 2-year follow-up, the injection group had significantly better scores on the modified Harris Hip Score (90.8 vs 84.2), Hip Outcome Score-Activities of Daily Living (88.4 vs 82.4), Hip Outcome Score-Sports Subscale (71.9 vs 64.1), 12-item International Hip Outcome Tool (83.9 vs 76.1), and visual analog scale for pain (1.2 vs 2.0) (all P < .001). Minimal clinically important difference rates were high in both groups, with higher rates in the injection group for modified Harris Hip Score (93% vs 77%; P = .033) and Hip Outcome Score-Activities of Daily Living (91% vs 75%; P = .042). PASS and SCB rates were significantly higher in the injection group across all patient-reported outcome measures (all P < .05). Revision and complication rates were low and did not differ significantly between groups. Conclusion Both groups improved significantly after arthroscopic subspine decompression. However, patients with a positive ultrasound-guided diagnostic AIIS injection achieved higher PASS and SCB rates than those selected by CT morphology alone, suggesting that injection-confirmed SSI may improve patient selection for subspine decompression.